The Reliability of a Computer-Assisted Telephone Interview Version of the Ohio State University Traumatic Brain Injury Identification Method. Issue 1 (January 2016) - Cuthbert, Jeffrey P.; Whiteneck, Gale G.; Corrigan, John D.; Bogner, Jennifer
Abstract : Objectives: Provide test-retest reliability (>5 months) of the Ohio State University Traumatic Brain Injury Identification Method modified for use as a computer-assisted telephone interview (CATI) to capture traumatic brain injury (TBI) and other substantial bodily injuries among a representative sample of noninstitutionalized adults living in Colorado. Design: Four subsamples of 50 individuals, including people with no major lifetime injury, a major lifetime injury but no TBI, TBI with no loss of consciousness, and TBI with loss of consciousness, were interviewed using the CATI Ohio State University Traumatic Brain Injury Identification Method between 6 and 18 months after an initial interview. Participants: Stratified random sample of Coloradans ( n = 200) selected from a larger study of TBI. Primary Measures: Cumulative, Severity and Age-related indices were assessed for long-term reliability. Cumulative indices were those that summed the total number of specific TBI severities across the lifetime; Severity indices included measures of the most severe type of injury incurred throughout the lifetime; and Age-related indices assessed the timing of specific injury types across the lifespan. Results: Test-retest reliabilities ranged from poor to excellent. The indices demonstrating the greatest reliability were Severity measures, with intraclass correlations for ordinal indices ranging from 0.62 to 0.78 and Cohen κ ranging from 0.50 to 0.62. One Cumulative outcome demonstrated high reliability (0.70 for number of TBIs with loss of consciousness ≥30 minutes), while the remaining Cumulative outcomes demonstrated low reliability, ranging from 0.06 to 0.21. Age-related test-retest reliabilities were fair to poor, with intraclass correlations of 0.38 to 0.49 and Cohen κ of 0.32 and 0.34. Conclusion: The CATI-modified Ohio State University Traumatic Brain Injury Identification Method used in this study is an effective measure for evaluating the maximum TBI severity incurred throughout the lifetime within a general population survey. The CATI measure is not recommended for use in determining cumulative counts of lifetime incidence of TBI. Abstract : Supplemental Digital Content is Available in the Text.